Coordination of Stunting Prevention and Mitigation in East Mawasangka District, Central Buton Regency - Siti Sarah; Sry Muyanita; Mahyudin (al-Afkar, Journal For Islamic Studies, 2026)
Stunting is one of the major public health issues that requires comprehensive handling through effective coordination among various stakeholders. This study aims to examine the coordination efforts for stunting prevention in Mawasangka Timur Subdistrict, Central Buton Regency. The research method focuses on analyzing coordination using three main indicators: Agency Effort, Unity of Action, and Common Purpose. The results of the study show that relevant agencies such as the Community Health Center (Puskesmas), the Health Department, and posyandu (integrated health service post) cadres have undertaken various efforts to combat stunting. These include the formation of coordination teams, public outreach, child growth monitoring, and improvement of health services. However, challenges remain, such as overlapping duties, lack of synergy, and limited resources. Unity of action is reflected through active collaboration between village midwives and posyandu cadres in health education, data recording, growth monitoring, and early reporting. A common purpose is demonstrated through coordination between health workers, village governments, and active community participation in nutritional education, child development monitoring, and empowerment of mothers with toddlers. Despite facing obstacles such as low public awareness and limited facilities, the presence of harmonious coordination and open communication among stakeholders shows a strong effort to align actions towards a shared goal of reducing stunting rates and ensuring a healthy, stunting-free generation of children.